Prognostic performance of the NRS2002, NUTRIC, and modified NUTRIC to identify high nutritional risk in severe acute pancreatitis patients - Chen, Dayu; Zhao, Bing; Wang, Linyu; Qiu, Yusi; Mao, Enqiang; Sheng, Huiqiu; Jing, Feng; Ge, Weihong; Bian, Xiaolan; Chen, Erzhen; He, Juan (Frontiers in Nutrition, 2023)
Background: Acute pancreatitis (AP) is the most common gastrointestinal disease requiring hospital admission. AP patients are categorized as mild, moderately severe and severe AP (SAP). For SAP patients, malnutrition increases susceptibility to infection and mortality. The Nutritional Risk Screening 2002 (NRS 2002), the Nutrition Risk in Critically Ill (NUTRIC) score and modified Nutrition Risk in Critically Ill (mNUTRIC) are nutritional risk screening tools of critically ill patients and have not been validated in patients with SAP. It is essential to evaluate the prognostic performance of these nutritional risk screening tools. Materials and methods: A retrospective study was designed to validate the NRS 2002, NUTRIC and mNUTRIC when applied to SAP patients. Receiver operating characteristic curves were plotted to investigate the predictive ability of clinical outcomes by comparing areas under the curve (AUC). Appropriate cut-offs were calculated by using Youden’s index. Patients were identified as being at high nutritional risk according to the calculated cut-off values. The effects of different scoring systems on mortalities were calculated using the Cox proportional hazards model. Logistic regression was used to assess the association between the energy provision and 28-day mortality. Results: From January 2013 to December 2019, 234 SAP patients were included and analyzed. Patients categorized as high nutritional risk by the NRS 2002 (12.6% versus 1.9% for 28-day and 20.5% versus 3.7% for 90-day), NUTRIC (16.2% versus 0.0% for 28-day and 27.0% versus 0.0% for 90-day) and mNUTRIC (16.4% versus 0.0% for 28-day and 26.4% versus 0.8% for 90-day) had significant higher mortality than those categorized as low nutritional risk. The NUTRIC (AUC: 0.861 for 28-day mortality and 0.871 for 90-day mortality,both cut-off value ≥ 3) and mNUTRIC (AUC: 0.838 for 28-day and 0.828 for 90-day mortality,both cut-off value ≥ 3) showed better predictive ability of the 28- and 90-day mortality than the NRS 2002 (AUC: 0.706 for 28-day mortality and 0.695 for 90-day mortality,both cut-off value ≥ 5). Conclusions: The NRS 2002, NUTRIC, and mNUTRIC scores were predictors for the 28- and 90-day mortalities. The NUTRIC and mNUTRIC showed better predictive ability compared with the NRS 2002 when applied to SAP patients.